Indoor Air Quality and Cognitive Performance - Steffen Künn; Juan Palacios; Nico Pestel (Institute of Labor Economics (IZA), 2019)
This paper studies the causal impact of indoor air quality on the cognitive performance of individuals using data from official chess tournaments. We use a chess engine to evaluate the quality of moves made by individual players and merge this information with measures of air quality inside the tournament venue. The results show that poor indoor air quality hampers cognitive performance significantly. We find that an increase in the indoor concentration of fine particulate matter (PM2.5) by 10 μg/m3 increases a player's probability of making an erroneous move by 26.3%. The impact increases in both magnitude and statistical significance with rising time pressure. The effect of the indoor concentration of carbon dioxide (CO2) is smaller and only matters during phases of the game when decisions are taken under high time stress. Exploiting temporal as well as spatial variation in outdoor pollution, we provide evidence suggesting a short-term and transitory effect of fine particulate matter on cognition.
Keywords: D91; I1; J24; Q50; Z20; 330; indoor air quality; cognition; worker productivity; chess